Passive-aggressive resistance against apartheid at the federal theological seminary of Southern Africa - Duncan, G. (Faculty of Theology, University of the Free State, 2013)
The passive aggressive behaviour theory of de Angelis (2009) combined with the "hidden transcript" theory of Scott (1985, 1990) and the racial conflict theory of Himes (1971) provide a theoretical framework for understanding resistance to apartheid in South Africa as a protective mechanism. The specific focus of this paper is passive-aggressive resistance centred at the Federal Theological Seminary of Southern Africa (Fedsem). This was demonstrated in both overt and covert forms of behaviour in the educational approach developed at Fedsem, its worship life and spirituality and demonstrations.
Keywords: Passive-aggressive resistance; Apartheid; Fedsem